Gambaran Pemeliharaan Pengguna Gigi Tiruan Cekat - Azalia Harira, Talitha; Pragustine, Yenny (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Loss of one or more teeth is a problem that often arises in the oral cavity. One way to replace missing teeth can be with fixed dentures. Patients with fixed dentures require regular lifelong care by maintaining dental and oral health. Many patients do not clean their fixed dentures properly and are often diagnosed with periodontitis. Objectives: To find out the description of maintenance in patients who wear fixed dentures. Methods: This study is a descriptive observational study with a cross-sectional design to describe the maintenance of patients who wear fixed dentures. A total of 35 patients using fixed dentures who visited the Smile Line Clinic and were willing to participate in the study were included in the study population. Results: Most of the fixed denture users in this study were female respondents by 65.7%, and respondents with higher education by 80%. 71,4% of respondents cleaned underneath their dentures, 54,3% used special tools, and 62,9% attended routine visits. Conclusion: Based on the results, the majority of patients using fixed dentures at a private clinic in DKI Jakarta have good maintenance of their fixed dentures.